2004
DOI: 10.1002/anie.200460241
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Whole‐Cell Biotransformation in a Biphasic Ionic Liquid/Water System

Abstract: Biocompatible ionic liquids act as a substrate reservoir and an in situ extracting agent in biotransformations with whole cells (see scheme). In the reduction of 4‐chloroacetophenone to (R)‐1‐(4‐chlorophenyl)ethanol, high product concentration (82 g L−1) and purity (99.6 % ee) were achieved without the addition of cofactors and without damaging the biocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(111 citation statements)
references
References 31 publications
0
104
1
3
Order By: Relevance
“…Biocompatible ILs can act as a substrate reservoir and an in situ extracting agent in biotransformations with whole cells (34). In the reduction of 4-chloroacetophenone to (R)-1-(4-chlorophenyl)ethanol, high product concentration (82 g/L −1 ) and purity (99.6% ee) were achieved without the addition of cofactors and without damaging the biocatalyst.…”
Section: Extractionmentioning
confidence: 99%
“…Biocompatible ILs can act as a substrate reservoir and an in situ extracting agent in biotransformations with whole cells (34). In the reduction of 4-chloroacetophenone to (R)-1-(4-chlorophenyl)ethanol, high product concentration (82 g/L −1 ) and purity (99.6% ee) were achieved without the addition of cofactors and without damaging the biocatalyst.…”
Section: Extractionmentioning
confidence: 99%
“…It was shown that the reaction of 2-octanone reduction to 2-octanol catalysed by alcohol dehydrogenase is faster when IL BMIM (CF 3 SO 2 ) 2 N is present in comparison to organic solvent applied so far (Eckstein et al, 2004). Additional beneficial effects of ILs is reduction of the toxicity towards the cell and possibility of their application in whole-cell biocatalysis (Weuster-Botz, 2007;Pfruender et al,. 2004).…”
Section: Liquid-liquid Extraction By Hydrophobic Ionic Liquidsmentioning
confidence: 99%
“…As they do not satisfy the requirements for the matrix used in MALDI-MS, a large number of ILs that exhibit excellent properties in many applications were excluded from use as the matrix in MALDI-MS. For example, MALDI-MS might be a powerful tool for monitoring the reactions or analyzing the reaction products of many biocatalytic reactions that take place in ILs [120,121], but the ILs employed in these reactions do not qualify as MALDI-MS matrices. Using laser desorption/ionization (LDI) and MALDI-MS, Masoud et al [122] 4 ], and studied their application to the analysis of amino acids, peptides and proteins dissolved in these solvents in the presence of other matrix substances such as SA, DHB and CCA.…”
Section: For Maldi-ms Analysismentioning
confidence: 99%